СИНЕРГИЗМ И АНТАГОНИЗМ В ГЕМИПОПУЛЯЦИЯХ НЕМАТОДЫ Rhabdias bufonis ОТ ОСТРОМОРДОЙ ЛЯГУШКИ (Experimental biology, 2015)
On the ground of morphological measurement above the several hundreds exemplars of ringworm Rhabdias bufonis from the frogs’ lung in was established that the sizes of the worms increase on the rising of their quantity in the host’s organism. In the smaller frogs and on the presence of the lung trematode Haplometra cylindracea number of 16-20 exemplars of R.bufonis is the threshold dose after which the intraspecific antagonism is beginning.
Keywords: host’s organism.